2019
DOI: 10.15585/mmwr.mm6831e1
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs: Pharmacy-Based Naloxone Dispensing — United States, 2012–2018

Abstract: Background: The CDC Guideline for Prescribing Opioids for Chronic Pain recommends considering prescribing naloxone when factors that increase risk for overdose are present (e.g., history of overdose or substance use disorder, opioid dosages ≥50 morphine milligram equivalents per day [high-dose], and concurrent use of benzodiazepines). In light of the high numbers of drug overdose deaths involving opioids, 36% of which in 2017 involved prescription opioids, improving access to naloxone is a public health priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 15 publications
4
122
0
Order By: Relevance
“…The countermeasures to limit the effects of the opioid epidemic focusing on limiting prescriptions have resulted in declining overdose deaths by prescription opioids mainly in the female population 16 . Finally, females were found to be more likely to obtain a naloxone prescription than males 21 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The countermeasures to limit the effects of the opioid epidemic focusing on limiting prescriptions have resulted in declining overdose deaths by prescription opioids mainly in the female population 16 . Finally, females were found to be more likely to obtain a naloxone prescription than males 21 .…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, we limited our causal trend analysis to data from January 2011 to December 2016. Some reports have indicated a decrease in deaths by opioid overdose in Ohio during the last semester of 2017 and early 2018, thought to be caused by decreased availability of carfentanyl in the illegal market and the wider availability of naloxone in Ohio and nationwide 21,24 . However, data for opioid overdose mortality data for 2018 are still not available, and there are no official reports for deaths in Ohio by drug overdose for 2018 currently available.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Furthermore, state naloxone dispensing rates and opioid overdose death rates are not correlated, which Freeman et al suggested should be addressed by "improving processes to increase dispensing to areas of need." 6 Guy et al 8 also emphasized disparities in naloxone dispensing and found that only 1 naloxone prescription was dispensed for every 69 high-dose opioid prescriptions nationally, with the lowest rates of dispensing in rural counties.…”
mentioning
confidence: 99%
“…Lin et al's findings echo a recent report from the Centers for Disease Control and Prevention (CDC) which found that despite increases in naloxone dispensing, only one of every 69 high-dose prescriptions was dispensed with a naloxone prescription. 2 A potential barrier identified in the CDC analysis was cost: two-thirds of naloxone prescriptions required out-of-pocket costs. Other barriers discussed by Lin et al include lack of clinician training and comfort with discussing the use of naloxone.…”
mentioning
confidence: 99%
“…From 2013 to 2017, drug overdoses increased in most states, 3 and of the 70,237 drug overdoses reported in 2017, two out of three overdoses involved opioids. 2 Although the rise in overdose deaths is largely attributed to illicit synthetic opioids, there remain important opportunities for primary care clinicians to prevent opioidrelated overdoses through naloxone prescriptions.…”
mentioning
confidence: 99%